A Separation: Breaking Up Is Hard to Do. Issue 1 (1st January 2020) - Yanof, Judith A.
ABSTRACT: A Separation is the 2011 award-winning film by Iranian writer-director Asghar Farhadi. Set in modern-day Tehran, the film is about an upper-middle class couple who are separating after 14 years of marriage. The filmmaker gives a nuanced portrayal of the complex dynamics in this family and, in particular, how the struggles of the adults painfully affect their 11-year old daughter, Termeh. A Separation is not formally told through the eyes of the child, however, the film's action and visual impact create in the audience a set of intense emotional reactions which powerfully convey Termeh's internal upheaval.